THE USE OF TIKTOK APPLICATION AS AN ONLINE ENGLISH LEARNING MEDIUM TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT SMA KATOLIK MESSAWA - Sari, Wiwin Novita; Dollah, Syarifuddin; G, Hasriani (JTechLP: Journal of Technology in Language Pedagogy, 2023)
The purpose of this research is to find out whether the use of TikTok Application as online English learning medium can improve students’ vocabulary mastery and to find out students’ perception of the use of TikTok Application in learning English vocabulary. This research was conducted at SMA Katolik Messawa. The population in this study were students of class X IPA SMA Katolik Messawa. The researcher used a purposive random sampling technique for class X IPA as the sample in this study. This study used a pre-experimental one group pretest posttest design method. The instrument used by the researcher is a vocabulary test and a questionnaire. Then several treatments were carried out and at the end of the meeting a vocabulary test was again carried out. Based on the results of the average calculation, it is known that the use of TikTok Application can improve students' vocabulary mastery, where the mean posttest is greater than the mean of pretest. Then the researcher concluded that the use of TikTok Application can improve students' vocabulary mastery. Students perceived the use of TikTok Application in learning English vocabulary quite positively. Their perceptions to the twelve statement items were dominated by positive responses, they surely have positive thoughts about the use of TikTok Application to improve their vocabulary mastery.